Drug Prescribing and Economic Analysis for Skin Diseases in Dermatology OPD of an Indian Tertiary Care Teaching Hospital: A Periodic Audit - KP, Bijoy; RS, Vidyadhar; P, Palak; SP, Chintan; PP, Atmaram (Indian Journal of Pharmacy Practice)
Dermatological problem in India manifests as primary and secondary cutaneous complaints. Among them allergy and itches are widely observed in most of the patients. Periodic auditing of prescriptions is essential to increase the therapeutic efficacy, decrease adverse effects, provide feedback to prescribers and analyze the observance of standards of medical treatment. Study objectives were to assess drug prescribing pattern and cost analysis in dermatology out patient department (OPD) in a tertiary care teaching hospital. The prescriptions from dermatology OPD were collected randomly by twice weekly survey for the duration of 6 months which were analyzed in consultation with clinical collaborators and evaluated using WHO drug use indicators. A total of 260 prescriptions were analyzed from 226 patients. Average drugs prescribed were 2.39/ prescription. Topical drugs (62.7%) were most commonly prescribed than systemic drugs (37.3%). Topical drugs were mostly in combination (26.66%) followed by antifungals (20.51%) and steroids (17.44%) alone. Antihistaminics (33.62%) commonly prescribed systemically followed by antifungals (22.41%) and antibiotics (20.69%). In 43.47% instances high potency steroids were prescribed while mild potency (15.22%) were least prescribed. Frequency of administration was specified in majority of prescriptions (99%) for topical administered drugs but dose/strength was specified in 54 (13.85%) prescriptions only. Average cost of drugs per prescription was found to be 196.74 INR. A great majority of drugs were prescribed in brand names. Though, dose/strength for topical drugs was inadequately mentioned but chances of error were negligible as the brand had availability in single dose/strength in pharmacy. Clinical Pharmacist can conduct such periodic audit to rationalize the prescription, reduce errors and suggest a cost effective management of skin diseases.
Keywords: Dermatology; Prescribing pattern; Outpatient; WHO indicators